Dietary Use of the Microalga Chlorella fusca Improves Growth, Metabolism, and Digestive Functionality in Thick-Lipped Grey Mullet (Chelon labrosus, Risso 1827) Juveniles - García-Márquez, Jorge; Galafat, Alba; Vizcaíno, Antonio Jesús; Barany, André; Martos-Sitcha, Juan Antonio; Mancera, Juan Miguel; Acién, Gabriel; Figueroa, Félix L.; Alarcón, Francisco Javier; Arijo, Salvador; Abdala-Díaz, Roberto Teófilo (Frontiers in Marine Science, 2022)
In recent years, a clear emphasis has been placed on replacing fishmeal and fish oil in aquafeeds with other alternative ingredients, including algae, particularly in low trophic omnivorous fish species. This work aimed at evaluating the effects of moderate dietary supplementation with the green microalga Chlorella fusca on growth, metabolism, and digestive functionality in juvenile thick-lipped grey mullet (Chelon labrosus). Fish were fed a control diet (CT) or a diet containing 15% C. fusca (C-15) biomass during 90 days. C. labrosus fed with the C-15 diet showed higher growth performance (in terms of final weight and length, weight gain, and specific growth rate) than the control group. Somatic indices and muscle proximate composition were similar at the end of the feeding trial. Regarding fatty acids profile, C. fusca-fed fish showed a selective retention of docosahexaenoic acid (DHA) in the liver, and arachidonic acid (ARA), eicosapentaenoic acid (EPA), and DHA in the muscle. Dietary inclusion of this microalga significantly increased intestinal total alkaline protease, leucine aminopeptidase, and alkaline phosphatase activities in specimens fed with C-15 diet. Furthermore, intestine histological analysis revealed the absence of damage signs on gut morphology in fish fed the microalgae supplemented diet. Thick-lipped grey mullets fed the C-15 diet increased plasma glucose and decreased plasma lactate. Overall, the effects observed on liver (lipid metabolism, glycolysis and glycogenolysis) enzyme activities, together with adequate fatty acid profile, metabolic response, and gut morphology, and a significant increase in the intestinal mucosa’s digestive and absorptive capacity, could explain the positive effects on growth performance obtained in fish fed the microalgae-supplemented diet. In conclusion, the results obtained showed that C. fusca is suitable as dietary ingredient for feeding thick-lipped grey mullet juveniles.